2018
DOI: 10.1016/j.polymdegradstab.2017.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Long term stabilization of PE by the controlled release of a natural antioxidant from halloysite nanotubes

Abstract: A natural antioxidant, quercetin, was adsorbed on the surface of halloysite nanotubes in various amounts to prepare a controlled release device. The combined additive was added to polyethylene providing antioxidant levels of 250, 500, 750 and 1000 ppm. All polymer samples contained 1000 ppm Sandostab PEPQ phosphonite secondary antioxidant as well. The stabilizing efficiency of quercetin was determined in processing experiments and by accelerated ageing. Quercetin proved to be a very efficient stabilizer of pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…The general conclusion was that HNT is a promising candidate for enzyme delivery processes; however, the substrate diffusion into the lumen and product release from it are often the limits of the HNT application as a carrier in enzyme immobilization. The HNTs have already proven to act as sufficient delivery agents for molecular antioxidants such as quercetin, 26 curcumin, 27 and resveratrol, 28 nevertheless, immobilization of antioxidant enzymes was not reported so far.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The general conclusion was that HNT is a promising candidate for enzyme delivery processes; however, the substrate diffusion into the lumen and product release from it are often the limits of the HNT application as a carrier in enzyme immobilization. The HNTs have already proven to act as sufficient delivery agents for molecular antioxidants such as quercetin, 26 curcumin, 27 and resveratrol, 28 nevertheless, immobilization of antioxidant enzymes was not reported so far.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Polyethylene (PE) is the most widely used thermoplastic polymer with applications in food packaging, cable and wire coatings, and agricultural industries. PE nanocomposites with HNTs showed unique and advanced engineering properties in addition to mechanical, thermal, and rheological improvements 4–10 . Tas et al reported that PE/HNT nanocomposite films can greatly contribute to food safety as an active food packaging material which can increase the shelf life of fresh food products and improve the quality of food products while limiting the consumption of chemical preservatives by increasing ethylene scavenging capacity and decreasing oxygen and water vapor transmission rates 11 .…”
Section: Introductionmentioning
confidence: 99%
“…PE nanocomposites with HNTs showed unique and advanced engineering properties in addition to mechanical, thermal, and rheological improvements. [4][5][6][7][8][9][10] Tas et al reported that PE/HNT nanocomposite films can greatly contribute to food safety as an active food packaging material which can increase the shelf life of fresh food products and improve the quality of food products while limiting the consumption of chemical preservatives by increasing ethylene scavenging capacity and decreasing oxygen and water vapor transmission rates. 11 Furthermore, due to the nontoxic nature of HNTs, they are a far better candidate than expensive and toxic tubular fillers like carbon nanotubes (CNTs), especially for food packaging applications.…”
Section: Introductionmentioning
confidence: 99%
“…[ 11,12 ] To circumvent this problem, capturing free radicals (aromatic amines, phenols, and loaded antioxidants) is the most common way for anti‐aging. [ 13–20 ] However, the problem that the damaged structure brings about the deterioration of properties is not solved by the conventional anti‐aging methods. [ 21–23 ] To date, it remains a huge challenge to make up for the deterioration of properties caused by the damaged structure.…”
Section: Introductionmentioning
confidence: 99%